Cognitive mechanisms in adolescent and young adult cancer patients and survivors: feasibility and preliminary insights from the cognitions and affect in cancer resiliency study - Kosir, U; Wiedemann, M; Wild, J; Bowes, L (Mary Ann Liebert, 2019)
This cross sectional pilot study assesses the feasibility of conducting online research into cognitive mechanisms in adolescent and young adult cancer populations. Twenty-one participants, aged 18–39 years, answered questionnaires about mental defeat, rumination, cancer worry, anxiety, and experience participating in such research. Seven participants scored in the clinical range for anxiety. Cancer-related worry was common. Rumination and mental defeat were positively associated with anxiety. The participants reported the length and type of questions to be appropriate and not distressing. Findings may inform future research into cognitive mechanisms, which could aid the development of psychosocial interventions for young cancer patients.